PROBLEM PENDIDIKAN ISLAM DALAM PERSPEKTIF GLOBALISASI - Syafrawi, Syafrawi (Universitas Islam Madura, 2016)
World Education in Indonesia in particular has Facing Many obstacles and challenges , The quantity is big individual and Families recognize the urgent Role of Family Singers, then they form a wider network for review Building synergy , then The Fast growing awareness competitive in the Central - Eastern nation kita thus able to compete in the globalization wave singer differences . Indonesia Education Needed Now the singer is the vision , repositioning strategy , the leadership of Dan . Without IT ALL , kita will NOT EVER move from the transformation of Yang Continuously rotating - turn . Searching Google Articles vision Obviously , Stages - Stages Yang Also Obviously , Dan commitment ALL LEADERSHIP Strong As well as the parties to the review reached ITU , 2020 Not NOT possibly Indonesia also can Risen Back Being a nation of dignity and victorious as the winner of globalization hearts .